2022
DOI: 10.1038/s41598-022-08163-7
|View full text |Cite
|
Sign up to set email alerts
|

Preferential stimulation of melanocytes by M2 macrophages to produce melanin through vascular endothelial growth factor

Abstract: Post-inflammatory hyperpigmentation is a skin discoloration process that occurs following an inflammatory response or wound. As the skin begins to heal, macrophages first exhibit a proinflammatory phenotype (M1) during the early stages of tissue repair and then transition to a pro-healing, anti-inflammatory phenotype (M2) in later stages. During this process, M1 macrophages remove invading bacteria and M2 macrophages remodel surrounding tissue; however, the relationship between macrophages and pigmentation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…hiPSCs culture was performed as described previously (22)(23)(24). Cells were maintained in Essential 8 (E8) medium (Thermo Fisher Scienti c, Waltham, MA, USA) on vitronectin-coated dishes (Thermo Fisher Scienti c), and attached cells were maintained at 37°C in 5% CO 2 .…”
Section: Methods Hipscs Culturementioning
confidence: 99%
“…hiPSCs culture was performed as described previously (22)(23)(24). Cells were maintained in Essential 8 (E8) medium (Thermo Fisher Scienti c, Waltham, MA, USA) on vitronectin-coated dishes (Thermo Fisher Scienti c), and attached cells were maintained at 37°C in 5% CO 2 .…”
Section: Methods Hipscs Culturementioning
confidence: 99%
“…ALDH2*1/*1-and ALDH2*1/*2-hiPSCs were generated from peripheral blood mononuclear cells (PBMCs) using a previously described reprogramming method, which involved serial centrifugation and Sendai viruses (Fig. 1A) (12,13). The cells were cultured in vitro nectin-coated dishes (Thermo Fisher Scientific).…”
Section: Generation and Culture Of Hipscmentioning
confidence: 99%
“…Tyrosinase (TYR) functions as a rate-limiting enzyme in melanin production [38]. Oxidation of L-DOPA by intracellular cell lysate is frequently used to estimate TYR activity [39][40][41][42]. However, the studies by Schallreuter et al [43], Land et al [44], and Plonka et al [45] reported that tyrosinases require L-DOPA for their own activation and may not produce dopaquinone via DOPA.…”
Section: L-dopa Oxidationmentioning
confidence: 99%
“…L-DOPA oxidation was measured as previously described methods with slight modifications [39][40][41][42]. B16F10 cells (5 × 10 4 cells) were seeded at 2 mL per well in two 6-well plates and incubated at 37 • C and 5% CO 2 for 18 h. The cells were then treated with α-MSH (200 nM) alone or with three different concentrations (20,40, and 80 µM) of ITA or DMI and further incubated for 72 h at 37 • C and 5% CO 2 .…”
Section: L-dopa Oxidationmentioning
confidence: 99%